New challenge confronting social scientists in IARCs with ecoregional mandates - Smith, J. (1994)
A meeting was held of social scientists from the International Agriculture Research Centers (IARCs) of the Consultative Group on International Agricultural Research (CGIAR), at the International Service for National Agricultural Research (ISNAR) in the Hague, Netherlands, in August 1992. The meeting was prompted by changes taking place within the CGIAR system towards increased investment in natural resource management research and emerging needs for closer collaboration among the IARCs. The meeting addressed issues identified by the social scientists concerning their roles in the CGIAR. It focused on the following themes: Global germplasm and ecoregional research mechanisms Links with national systems and policy research The users' perspectives: Factoring farmers' needs into the research agenda Sustainability issues in agricultural research Socioeconomic data bases, priority-setting, and impact assessment These five themes were supported by short "issues" papers, by presentations from center scientists and three invited speakers, and by working groups with subsequent plenary discussion sessions. This proceeding is divided into the summaries of the papers and the discussion groups' conclusions for each theme. The text from the invited speakers follows the five theme sections.